Expectativas de jovens negros quanto ao acesso à Universidade: o caso de uma escola da Zona Norte de São Paulo - Nascimento, Tarcisio Antonio do (Universidade Federal de São Carlos, 2006)
This work is about a quantitative research, having as objective to analyze the young black in the region north of the city of São Paulo, searching to understand the difficulties found for these in the access the university. The biggest difficulty pointed for the participants is the lack of financial resources, making with that these young has that to dedicate to the work, taking them not to get it good notes, for the lack of time to the study, pointed for them also as the second difficulty with respect to the access to superior education. The research discloses that practically the half of the young blacks has interest in the continuity of the studies, exactly not having financial incentives on the part of familiar, resources and social support. The study it points the necessity of the creation of Affirmative Politics that reach the black and poor white in Secondary Education.
Keywords: Educação; Ensino de segundo grau; Escolas públicas; Negros; Acesso a universidade; Education; Secondary education; Public school; Black; Access the university; CIENCIAS HUMANAS::EDUCACAO